(untitled) - Balanko-Dickson, Greg (New York, 2007)
Tips & Traps for Writing an Effective Business Plan uses the popular Tips & Traps format to guide you step by step through the process of creating an effective plan that will work with a developing business. You'll learn how to assemble information and write each part of your plan, with the goal of having a ready-to-go, working strategy in just 30 days. The book also provides specific advice for crafting plans that apply to different industries and also includes detailed instructions for writing a financial plan
Keywords: Business planning,Business writing,Lập kế hoạch kinh doanh,Ghi chép trong kinh doanh